Reconstructing optimism in addiction recovery: spirituality, therapeutic community, and identity transformation - Fitniwilis Fitniwilis; Mohamad Isa bin Amat; Muhammad Khairi bin Mahyuddin (Journal of Counseling, Education and Society, 2026)
Recovering from addiction is more than just stopping the consumption of substances; it is also about regaining a sense of self and future. One psychological resource that has been consistently recognized for its role in supporting recovery is optimism. On one hand, optimism can be thought of as a stable individual characteristic; but more importantly, it is closely linked to the social and spiritual settings of recovery. Therefore, the purpose of the research is to investigate how the concept of optimism gets reshaped by the experiences of the spiritual elements, therapeutic community, and personal identity transformation that are integral aspects of addiction recovery. For data collection, the method involved was qualitative interpretive and reflexive thematic analysis was utilized for the purpose of data analysis. Four participants were purposively selected to yield information-rich, in-depth accounts, following the information-power rationale for small-sample qualitative interview studies (Malterud et al., 2016) rather than a probability-based logic of generalization. Data were obtained through detailed semi-structured interviews of four subjects who either had undergone rehabilitation within spiritually-based therapeutic communities or were still doing their program. These data were subjected to an analyzing software called MAXQDA which allows a researcher to go through a series of coding procedures for data to find meaning, psychosocial-spiritual dynamics, etc., as a reflection of participants' life stories. Results showed that one's sense of optimism and being in control of their recovery are rooted in belief in oneself, motivation from moral and emotional values, a caring social environment, and hopes for a meaningful and fulfilling life ahead. Besides that, optimism works as a resource that can be transformed as it contributes to the development of personal confidence (self-efficacy), emotional equilibrium, spiritual well-being as well as community's common strength (collective resilience). This paper adds to the field of recovery science and offers optimism as a psychosocial-spiritual process which is dynamic, relational and contextual in addiction recovery context.